Cover Image, Volume 56, Number 12, December 2021. Issue 12 (29th November 2021) - Hoekstra, Nadia E.; Dannull, Kimberly A.; Weinman, Jason P.; Liptzin, Deborah R.; Hinds, Daniel M.
Abstract : Cover Caption: The cover image is based on the Letter to the Editor Vaping and diffuse alveolar hemorrhage: All EVALI is not created equal by Nadia E. Hoekstra et al., https://doi.org/10.1002/ppul.25675 .